Strategic Determinants of Solar Energy Innovation Uptake in Nairobi City County, Kenya - Agandi, Victor; Makau, Godfrey (European Journal of Business and Strategic Management, 2023)
Purpose: The purpose of the study was to investigate the strategic determinants of solar energy innovation uptake in Nairobi City County, Kenya. Methodology: The study adopted a descriptive research design. The entire population of the study therefore, comprised the 521 solar energy dealers registered with Electrical and Petroleum Regulatory Authority (EPRA) as at May 2021 categorised as (technicians (214) and contractors (307) solar energy dealers from which 156 dealers sample size was taken through mixed methods before self-administered survey questionnaires were given for collecting the primary data. Secondary data was also reviewed from county government, EPRA and others sources publishing on solar energy regulations and market trends. Statistical package for social sciences (SPSS) was also used to aid in analysis. Descriptive statistics and regression analysis were used to analyze the data that had been obtained. The data was presented in form of tables. Findings: The study established that in terms of ranking, technological factors are strongest in explain solar innovations uptake in Kenya followed by the solar innovation product/service quality factors and organizational factors with environmental factors emerging least critical. It therefore recommends various administrative, legislative and further academic research actions to promote green marketing strategy as a best practice continuous improvement strategic management practice, encourage consumption of eco-friendly solar products and mitigate over adverse effects of solar energy technology equipment after their end of life and more research to understand why environmental factors emerged to have least influence and hence unpack some complexities that this study was unable to establish. Unique Contribution to Theory, Practice and Policy: The study was anchored on institutional theory. The study recommended that a similar national level studies be undertaken and with more stakeholders involved. In so doing, opinions of more Kenyans regarding the future of solar innovations adoption and utilization could be explored within the green marketing strategy concept. Generally, the study provides the necessary information for the Government of Kenya and other stakeholders in determining the future of solar PV energy uptake strategic determinants and green marketing strategy ramifications in the country.